Characteristics of Physical Exercise Programs and Their Effects on Quality of Life and Functional Capacity in Individuals with Chronic Obstructive Pulmonary Disease: A Scoping Review - Rafael Oliveira; João Paulo Brito; Halil İbrahim Ceylan; Maria de Brito Soares; Alexandre Duarte Martins; Tiago Vasconcelos; João Moutão; Susana Alves (Medicina)
Background and Objectives: Individuals with chronic obstructive pulmonary disease (COPD) often exhibit some degree of intolerance to physical exercise and several limitations in daily activities. Therefore, the objective of this study was to conduct a scoping review on the characteristics—frequency, intensity, time, and type (FITT)—and the effects of exercise programs on quality of life and functional capacity in individuals with COPD. Materials and Methods: The present review included 21 studies that were scoping-reviewed to describe their main findings and training characteristics. Results: The participants across studies ranged in age from ~39 to 76 years with mild to very severe COPD stages. The results showed that, among all studies, eleven used cardiorespiratory training (e.g., walking or cycling), five used strength training (e.g., exercises with elastic bands or traditional resistance training), and five implemented combined training (i.e., cardiorespiratory and strength exercises). Conclusions: Overall, all training protocols improved aerobic capacity (cardiorespiratory training), strength (resistance training), and both capacities together (combined training). In conclusion, this review provided complementary insights to existing exercise prescription guidelines, particularly concerning cardiorespiratory, strength, and combined training in individuals with COPD. However, the methodologies of the training protocols varied widely, and detailed descriptions of FITT components were often incomplete or lacking clarity, especially regarding the specific exercises used. Future research should include more comprehensive spirometry variables such as forced expiratory volume 1 or forced vital capacity, as these are critical for determining COPD stages. Thus, there is a clear need for more high-quality research with robust methodological design in the context of exercise interventions for individuals with COPD.